Питання інформаційної безпеки України на сучасному етапі - Войціховський, А. В.; Voytsihovskyi, A. V.; Андрій Войціховський (Право і безпека. - 2015. - № 3 (58). - С. 15–20., 2015)
Досліджено сутність інформаційної безпеки України, засоби її реалізації, джерела загроз інформаційній безпеці України, шляхи забезпечення інформаційної безпеки України на сучасному етапі суспільного розвитку.

Nowadays the spread of the facts concerning unlawful collection and use of information, unauthorized access to information resources and others is of serious concern. The issues of guaranteeing information security have become very important for Ukraine, which faced a hybrid information war. The objective of this research paper is to detect and analyze the main directions of state information policy aiming at protection of the national information space, as well as to reveal the sources of threats to information security of Ukraine and to find the ways to ensure information security of Ukraine at the present stage of social development. Information security of Ukraine as an important component of the national security system provides preventive activities of state authorities to provide guarantees of information security to individuals, social groups and society in the whole and is aimed at achieving sufficient level of spiritual and intellectual potential for the development of the state and social progress. Active cooperation between Ukraine and NATO in the field of information security is noted. It is reasonably determined that an important group of measures of guaranteeing information security are measures to protect the national information space from unauthorized interventions, as well as control over the formation of mass consciousness. As a result it is indicated that the formation and implementation of state policy for the protection of national interests against the threats in the information sphere, the adoption of relevant legislative acts, coordination of the activities of state authorities in the field of ensuring information security will consistently contribute to bringing Ukrainian national information security system in line with international standards in this area.

Исследованы сущность информационной безопасности Украины, средства её реализации, источники угроз информационной безопасности Украины, пути обеспечения информационной безопасности Украины на современном этапе общественного развития.
Keywords: Міжнародне право .International Law. Международное право; Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; інформація; інформаційна безпека; інформаційний простір; співробітництво; Організація Північноатлантичного Договору (НАТО); НАТО; information; information security; information space; cooperation; North Atlantic Treaty Organization (NATO); NATO; информация; информационная безопасность; информационное пространство; сотрудничество; Организация Североатлантического договора (НАТО)